A novel citizen science approach for large-scale standardised monitoring of bat activity and distribution, evaluated in eastern England. (November 2015) - Newson, Stuart E.; Evans, Hazel E.; Gillings, Simon
Abstract: In many countries, bats have high conservation prioritisation owing to their trophic position, habitat associations and threat level, and many have dedicated management plans. However, poor knowledge of species' ecology, identification issues and surveying challenges mean that large-scale monitoring to produce required distribution and abundance information is less developed than for some other taxa. Static detectors deployed to record bats throughout whole nights have been recommended for standardised acoustic monitoring but to date their cost has prohibited wide uptake. Here we describe an extensive survey approach in which members of the public borrowed detectors to participate in a large-scale monitoring and mapping project. Covering a 15% sample of the study area over two years, the survey generated over 600, 000 bat recordings. We describe a semi-automated step-wise method for processing this large volume of recordings to assign identity to species or genus level with low error rates. Twelve species were recorded during the survey, ranging from the near ubiquitous Common Pipistrelle Pipistrellus pipistrellus to the locally scarce Leisler's bat Nyctalus leisleri . We show pronounced patterns of seasonality consistent with post-breeding dispersal and new information on nocturnal activity patterns. Using regression trees we generate new maps of standardised variation in activity which is likely to reflect underlying spatial variation in relative abundance. These reveal hitherto unknown patterns for species of superficially similar status. We conclude that with logistical support and centralised automated species identification it is now possible for the public to contribute to acoustic bat monitoring at an unprecedented scale. Highlights: We describe a novel citizen science approach for extensive standardised recording of bats. Over 600, 000 bat recordings were generated over two years. A semi-automated step-wise method for assigning recordings to species is presented. Pronounced seasonal patterns consistent with post-breeding dispersal are shown. Maps of activity were produced which are likely to reflect underlying spatial variation in relative abundance.